Unfolding anti-tumor immunity: ER stress responses sculpt tolerogenic myeloid cells in cancer. Issue 1 (17th January 2017) - Cubillos-Ruiz, Juan R.; Mohamed, Eslam; Rodriguez, Paulo C.
Abstract : Established tumors build a stressful and hostile microenvironment that blocks the development of protective innate and adaptive immune responses. Different subsets of immunoregulatory myeloid populations, including dendritic cells, myeloid-derived suppressor cells (MDSCs) and macrophages, accumulate in the stressed tumor milieu and represent a major impediment to the success of various forms of cancer immunotherapy. Specific conditions and factors within tumor masses, including hypoxia, nutrient starvation, low pH, and increased levels of free radicals, provoke a state of "endoplasmic reticulum (ER) stress" in both malignant cells and infiltrating myeloid cells. In order to cope with ER stress, cancer cells and tumor-associated myeloid cells activate an integrated signaling pathway known as the Unfolded Protein Response (UPR), which promotes cell survival and adaptation under adverse environmental conditions. However, the UPR can also induce cell death under unresolved levels of ER stress. Three branches of the UPR have been described, including the activation of the inositol-requiring enzyme 1 (IRE1), the pancreatic ER kinase (PKR)-like ER kinase (PERK), and the activating transcription factor 6 (ATF6). In this minireview, we briefly discuss the role of ER stress and specific UPR mediators in tumor development, growth and metastasis. In addition, we describe how sustained ER stress responses operate as key mediators of chronic inflammation and immune suppression within tumors. Finally, we discuss multiple pharmacological approaches that overcome the immunosuppressive effect of the UPR in tumors, and that could potentially enhance the efficacy of cancer immunotherapies by reprogramming the function of tumor-infiltrating myeloid cells.